Correlation between Cortical Excitability and Hand Function in Patients with Subacute Cerebral Infarction - Ling CHEN; Junling WANG; Dongfeng HUANG (康复学报)
Objective:To observe the cortical activation characteristics of cerebral motor prediction in patients with subacute cerebral infarction in the palm grasping task, and to explore the correlation between cortical excitability and hand function in patients with cerebral infarction.Methods:A total of twenty-five patients with subacute cerebral infarction who were hospitalized in the first affiliated hospital of Sun Yat-sen University from January 2017 to March 2018 were selected as the experimental group, and twenty-five healthy individuals matched with the gender and age of the experimental group were selected as the control group.Event related potentials were used to collect the electroencephalogram signals of the two groups in the palm grasping task, and then analyzed the latencies and amplitudes of the contingent negative variation(CNV)in the cerebral cortex before motor activation.Action Research Arm Test(ARAT)was used to assess the function of hand, and the correlation between CNV amplitude and ARAT score was analyzed.Results:Compared with the control group, the CNV latencies in the midline region of the experimental group were significantly shorter during the left hand grasp and right hand grasp, and the CNV amplitude were statistically significantly increased in the midline, bilateral frontal lobe and primary motor area(M1)(P<0.05).There was no significant difference in CNV latency between left hand grasp and right hand grasp in the experimental group(P>0.05), with the CNV amplitude of Cz electrode in midline statistically significantly greater than that of C4 electrode in contralateral M1(P<0.05).There was moderate correlation between the CNV amplitude and ARAT in the non-lesioned frontal lobe, M1 and midline during right hand grasp in the experimental group(F4: r=0.510; C4: r=0.442; Fz: r=0.428).There was moderate correlation between the CNV amplitude and ARAT in the non-lesioned frontal lobe, M1 and midline during left hand grasp in the experimental group(F4: r=0.422; C4: r=0.496; Fz: r=0.446).Conclusion:The neural mechanism of motor anticipation in patients with subacute cerebral infarction is abnormal, the time of brain motor preparation is prolonged, and the non-lesioned frontal lobe and M1 are hyperactivity compensatory during motor anticipation.There was moderate correlation between the cortical excitability and hand dysfunction.Therefore, CNV may be a neural indicator of the severity of hand dysfunction in patients with cerebral infarction.